Putting the Brakes on Fear - Maren, Stephen (2013)
The extinction of fear is believed to involve inhibitory processes in the amygdala. In this issue of Neuron, Trouche et al. (2013) show that basal amygdala neurons activated by fear conditioning are silenced by local inhibitory interneurons after extinction.